Menyemai Generasi Penerus Bangsa melalui Pembelajaran Pendidikan Kewarganegaraan dengan Pendidikan Berkarakter - Sunaryati, Titin; Zahra, Anita; Zhafira, Alifya; Lailatul Fazriah, Izzah (SAP (Susunan Artikel Pendidikan), 2024)
Citizenship education is an integral part of the education curriculum, especially at the elementary school level, playing a crucial role in shaping students' characters. This research aims to identify the influence of citizenship education learning on students in their daily lives. The research method used is literature review with a descriptive approach. The findings of this study reveal how citizenship education learning can impact students in their real-life experiences. It is hoped that the results of this research will provide a better understanding of the importance of citizenship education in shaping students' characters and behaviors.